A new protocol for on-farm production of arbuscular mycorrhizal mass inoculum for rainfed upland rice - and M. VARIAR, D. MAITI*, M.K. BARNWAL, R.K. SINGH (Indian Phytopathology, 2009)
A mass inoculum production technique of arbuscular mycorrhizal fungi (AMF) of native consortium, in situ (under existing farm system), suitable for upland rice, technically feasible and economically viable for small and marginal upland farmers was developed. The protocol for mass production of inoculum was standardized and optimum dose (1.25-1.5 t/ha equivalent to 3.0-3.6 x 104 AMF infective propagules/m2) was worked out.